2008
DOI: 10.3923/pjbs.2008.1234.1239
|View full text |Cite
|
Sign up to set email alerts
|

Every-Other-Furrow Irrigation with Different Irrigation Intervals for Grain Sorghum

Abstract: The water stress effects caused by every-other-furrow irrigation on yield may be alleviated by more frequent irrigation intervals. This research was conducted to determine yield and water use efficiency of grain sorghum under fixed and variable every-other-furrow and every furrow irrigations at different irrigation intervals and shallow and deep water table conditions. Water needs of grain sorghum grown on a fine-texture soil may not be met by using Every-Other Furrow Irrigation (EOFI) especially under 15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 6 publications
7
11
0
Order By: Relevance
“…The substantial GY decrease in the AFI14 treatment may be due to the small amount of applied irrigation water, which did not match full corn water requirements, caused water stress, and consequently reduced crop yield. This finding is similar to results obtained by Sepaskhah and Khajehabdollahi (2005) and Sepaskhah and Ghasemi (2008) for grain sorghum. On the other hand, AFI with more frequent events at 7-d intervals (AFI7) proved to be superior by increasing GY by 8.9% more than EFI based on a two-season mean.…”
Section: Grain Yield (Gy)supporting
confidence: 92%
See 1 more Smart Citation
“…The substantial GY decrease in the AFI14 treatment may be due to the small amount of applied irrigation water, which did not match full corn water requirements, caused water stress, and consequently reduced crop yield. This finding is similar to results obtained by Sepaskhah and Khajehabdollahi (2005) and Sepaskhah and Ghasemi (2008) for grain sorghum. On the other hand, AFI with more frequent events at 7-d intervals (AFI7) proved to be superior by increasing GY by 8.9% more than EFI based on a two-season mean.…”
Section: Grain Yield (Gy)supporting
confidence: 92%
“…This may be attributed to the better availability of soil moisture during the irrigation cycle for AFI7 (Figure 1), which enhanced water and nutrient uptake and doubtless reflected on final GY. This result confirms the results found by Abdel-Maksoud et al (2002), Sepaskhah and Khajehabdollahi (2005), Sepaskhah and Parand (2006), Sepaskhah and Ghasemi (2008) for grain sorghum; Nasri et al (2010).…”
Section: Grain Yield (Gy)supporting
confidence: 92%
“…So, by applying a 35% water deficit, proper results could be obtained for WP. This agrees with different proposed water deficit percentages in different surface irrigation methods (Sepaskhah and Ghasemi, 2008;Sepaskhah and Hosseini, 2008;Sarai Tabrizi et al, 2012;Sepaskhah and Tafteh, 2012;Tafteh and Sepaskhah, 2012). Another important water management index is gross water productivity which depends mainly on irrigation efficiency (Perry, 2007;Heydari, 2014), and it is less affected by manner of water distribution.…”
Section: Determination Of An Almost Optimal Irrigation Schedule and Csupporting
confidence: 89%
“…It shows that the difference in okra crop yield obtained with CFI and AFI was non-significant (p>0.05). A slight reduction in crop yield with AFI compared to CFI was also reported by Majeedano (2012), Bakker et al (1995), Sepaskhah and Ghasemi (2008), and Rafiee and Shakarami (2010). Crabtree et al (1985) also found a yield reduction in sorghum and soybeans when using AFI.…”
Section: Resultsmentioning
confidence: 50%